The Influence of Safety and Comfort on Walkability in Erbil City Center - Shilan A. Nury; Hamid T. Haykal (Zanco Journal of Pure and Applied Sciences, 2023)
The designing and planning of walkable public open spaces are gaining popularity due to the numerous advantages they bring in terms of health, ecology, economics, and social interactions. It is noted that walkable city centers have become common topics not only among academics but also among the general public, especially in the fields of environmental and ecological concerns and transportation. Because of the lack of scientific evidence and understanding of public space walkability in the city center, the relationship between public open space design characteristics and walkability in Erbil city center has not been studied yet. Therefore, this study evaluated the influence of safety and comfort on walkability as factors related to public open space design characteristics in Erbil city center. For this purpose, three case studies were selected in Erbil city center and a combination of both subjective (questionnaire survey) and objective assessments (observation and checklist) was used. According to the results of the statistical analysis, it is revealed that there were substantial discrepancies in residents' contentment levels in different areas regarding walkability conditions in terms of the parameters examined, but there were no significant differences between the outcomes of the two measuring methods (subjective and objective) that were utilized.